Student Engagement: A Critical Conceptualisation of the Complexity of the International Students’ Experiences - Dangeni, - (Journal of International Students, 2023)
Increasing numbers of international students bring their different cultures, languages, and educational backgrounds to higher education, and they expect their experiences and interactions with higher education institutions to be rewarding journeys. A key issue - the dynamic and multifaceted concept of student engagement as an important indicator of the quality of the student experience - has yet to be thoroughly addressed in conceptual discussions and empirical studies with international students, and thus deserves more attention. This paper aims to conceptualise this buzzword, i.e., 'student engagement', in higher education, by embracing the complexity and diversity of international students' experiences to enable a deeper understanding of international students' experiences and needs, and to inform research and practice that considers all stakeholders through questions and suggestions.